1998
DOI: 10.1007/pl00013473
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Wavelength-Dependent Photochemistry in Bilirubins by Serum Albumin

Abstract: Quantum yields for Z > E photoisomerization of the natural bi-chromophore bilirubin IX in ammoniacal methanol solution were found to vary with excitation wavelength, whereas no variation (within experimental error) was observed for xanthobilirubic acid and for symmetrically substituted bilirubins (bilirubin III, bilirubin XIII, and mesobilirubin XIII) in the same solvent. The quantum yield for Z > E photoisomerization of xanthobilirubic acid bound to human serum albumin was also invariant with excitation wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The Φ ZE value is comparable to that of (Z)xanthobilirubic acid (Figure 1); Φ ZE ∼ 0.19 obtained in methanol containing 0.1% NH 4 OH (λ irr in the range of = 390− 470 nm). 17 The magnitudes of the Z → E and E → Z isomerization quantum yields for 1a were nearly the same in the irradiation wavelength range of 360−410 nm, but they increased approximately by a factor of 2 at longer irradiation wavelengths (490 nm). The observed dependence can be rationalized within the concept of nonequilibration of excited rotamers (NEER).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…The Φ ZE value is comparable to that of (Z)xanthobilirubic acid (Figure 1); Φ ZE ∼ 0.19 obtained in methanol containing 0.1% NH 4 OH (λ irr in the range of = 390− 470 nm). 17 The magnitudes of the Z → E and E → Z isomerization quantum yields for 1a were nearly the same in the irradiation wavelength range of 360−410 nm, but they increased approximately by a factor of 2 at longer irradiation wavelengths (490 nm). The observed dependence can be rationalized within the concept of nonequilibration of excited rotamers (NEER).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…The moist pellet from 10 to 15 million cells (∼20 μl) was mixed with 80–100 μl of 0.1 M di‐octamylamine acetate in methanol, sonicated, and centrifuged. Twenty microliters of the supernatant were chromatographed by reversed phase high‐performance liquid chromatography (HPLC) as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…These results are confirmed by its low fluorescence yields (Φ f < 5 × 10 −4 ), low yields of triplet states (<0.01), and the absence of efficient bleaching of the chromophore. 12,20,28,29 However, the relaxation processes of excited BR appear to be governed by complex mechanisms that are not fully known. 21 A few other studies at short time scales using femtosecond fluorescence upconversion measurements suggested that the initial deactivation process extends from the 100 fs to the 50 ps time scale, and the initial fast component was attributed to a conical intersection in the vicinity of the Franck−Condon region.…”
Section: Introductionmentioning
confidence: 99%